2017
DOI: 10.1007/s00299-017-2133-0
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic pigeonpea events expressing Cry1Ac and Cry2Aa exhibit resistance to Helicoverpa armigera

Abstract: Independent transgenic pigeonpea events were developed using two cry genes. Transgenic Cry2Aa-pigeonpea was established for the first time. Selected transgenic events demonstrated 100% mortality of Helicoverpa armigera in successive generations. Lepidopteran insect Helicoverpa armigera is the major yield constraint of food legume pigeonpea. The present study was aimed to develop H. armigera-resistant transgenic pigeonpea, selected on the basis of transgene expression and phenotyping. Agrobacterium tumefaciens-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…45,46 A major impetus for the mitigation of this pest in pigeonpea has been transgenesis due to the lack of availability of resistance sources in the cultivated germplasm. 47,48 Studies accruing from the literature, [14][15][16][17][18][19] including the work from our group, 15 have demonstrated the feasibility of curtailing this pest in pigeonpea using different Bt ICPs under laboratory conditions. However, there has not been a single report demonstrating the performance of these transgenic events under soil conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…45,46 A major impetus for the mitigation of this pest in pigeonpea has been transgenesis due to the lack of availability of resistance sources in the cultivated germplasm. 47,48 Studies accruing from the literature, [14][15][16][17][18][19] including the work from our group, 15 have demonstrated the feasibility of curtailing this pest in pigeonpea using different Bt ICPs under laboratory conditions. However, there has not been a single report demonstrating the performance of these transgenic events under soil conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The overall leaf damage ranged between 5 and 20% and demonstrated that most of the transgenic plants were effective in resisting the insect pest compared to wild type plants. Based on stringent evaluation of the transgenic plants for their efficacy against H. armigera under two different situations in the nethouse, ten transgenic pigeonpea events (cry2Aa events-7, 10,11,13,14;22,24,25,6) were shortlisted and selected as superior. Comparison of efficacy against herbivory versus the amount of cry protein in each of the events in both the experiments showed that leaf damage ranged between 9% and 27% in the soil experiment and 3% and 26.7% in the pot experiment ( Fig.…”
Section: Corroboratory Assessment Of Transgenic Plants Under Both Soimentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged incubation of shoots in root induction media resulted in the ageing which had a negative effect on normal growth and seed yield (Ghosh et al 2017). Though there are reports of various direct rooting protocols in black gram (Saini et al 2002;Muruganatham et al 2005;Harisaranraj 2008;Adlinge et al 2014), those protocols lack detailed information about the number of roots produced per explant and root length.…”
Section: Discussionmentioning
confidence: 99%